2018
DOI: 10.1111/cbdd.13337
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation on the binding modes of Rimonabant analogs with CB1 and CB2

Abstract: The human cannabinoid G-protein-coupled receptor 1 (CB1) is highly expressed in central nervous system. CB1-selective antagonists show therapeutic promise in a wide range of disorders, such as obesity-related metabolic disorders, dyslipidemia, drug abuse, and type 2 diabetes. Rimonabant (SR141716A), MJ08, and MJ15 are selective CB1 antagonists with selectivity >1,000-folds over CB2 despite 42% sequence identity between CB1 and CB2. The integration of homology modeling, automated molecular docking, and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Additionally, S123 (which is predicted to form hydrogen bonds with 16a in CB 1 ) is replaced by C40 at the equivalent position in CB 2 , which may affect hydrogen bond formation and promote CB 1 selectivity. These observations are congruent with the incompatibility of the CB 2 binding pocket geometry with the extended conformation of rimonabant, as it has been suggested in the literature …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, S123 (which is predicted to form hydrogen bonds with 16a in CB 1 ) is replaced by C40 at the equivalent position in CB 2 , which may affect hydrogen bond formation and promote CB 1 selectivity. These observations are congruent with the incompatibility of the CB 2 binding pocket geometry with the extended conformation of rimonabant, as it has been suggested in the literature …”
Section: Resultssupporting
confidence: 91%
“…These observations are congruent with the incompatibility of the CB 2 binding pocket geometry with the extended conformation of rimonabant, as it has been suggested in the literature. 56…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23 The investigation and determination of GPCR structures are hindered due to the nature of membrane proteins and the transient and dynamic interactions between GPCRs and their ligands, which are difficult to capture, and post-technical challenges. 24 Regarding CBs, currently there are only four resolved CB1 crystal structures and one resolved CB2 crystal structure in the Protein Data Bank. The lack of crystal structures, especially for CB2, is an obstacle that researchers have to overcome to explore their conformational change and downstream signaling when they are bound with agonists, antagonists, or even allosteric modulators at a topographically distinct binding site.…”
Section: Introductionmentioning
confidence: 99%
“…By applying molecular modeling simulations, a previous study reported for the first time the binding modes of rimonabant analogues with CB1 and CB2. 24 However, both reported structures of CB1 and CB2 in their inactive conformations were constructed from the crystal structure of the sphingosine-1-phosphate receptor 1 using homology modeling, and only four ligands with selectivity to CB1 or CB2 were involved. In this study, we investigated CB1 and CB2 in both the inactive and active conformations via molecular dynamics (MD) simulations and conducted free energy analysis with an aim to systematically compare the binding features, conformations, potency, and selectivity of the two cannabinoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 2016 release of the first CB 1 crystal structure increased the scope of modeling opportunities, homology modeling has continued to be an important approach to obtain accurate 3D structures in the absence of experimental structures, especially for the phytocannabinoids. In 2018, Liu and coworkers used a combination of sequence alignment and homology modeling of the S1P1 crystal structure (PDB: 3V2W ) ( Hanson et al., 2012 ) to investigate the binding modes of rimonabant analogs as selective inverse agonists/antagonists for CB 1 ( Liu et al., 2018 ). Their CB 1 model was validated by superimposing the model and the crystal structure ( PDB : 5TGZ ).…”
Section: Introductionmentioning
confidence: 99%